Comparison of External Costs of Diesel, LNG, and Electric Drive on a Ro-Ro Ferry Route - Vukić, Luka; Guidi, Giambattista; Poletan Jugović, Tanja; Oblak, Renato (Promet - Traffic&Transportation, 2021)
Following the sustainable transport policy, environmental criteria are becoming a competitive factor within the maritime shipping industry. The use of greener fuels in internal combustion engines, including electric drive, is a measure that can reduce external costs of transport. Alternative fuels in maritime transport, benefits, and potential attainable savings have been examined on the Kamenari–Lepatane ro-ro ferry route in the Bay of Kotor located in Montenegro. The results indicate higher total fuel cost savings by switching to LNG compared with electric power. However, the external costs of the latter are considerably lower, especially using renewable energy sources rather than fossil ones in the production process. The results obtained, relative to the magnitude and assumed complete internalization of external costs, justify the incentive to use the renewable sources as energy providers on the examined ro-ro ferry route. Environmental criteria should play a decisive role in assessing the overall benefit value, under the current trends and regulations of emissions reduction in maritime transport.